2019
DOI: 10.1002/ijc.32259
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second primary malignancy after breast cancer and related risk factors—Is breast‐conserving surgery safe? A nested case–control study

Abstract: Risk of second primary malignancy (SPM) is increasing. We aimed to assess the incidence and related risk factors of SPM among breast cancer (BC) patients from this nested case–control study using the SEER database. BC patients with SPM were identified as the case group and SPM‐free patients were defined as the control group. Propensity score matching of cases with controls by the year of the first primary BC diagnosis was conducted at the ratio of 1:5, and 97,242 BC patients were enrolled from 1998 to 2013 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…In Our results showed that breast cancer as the second primary cancer was associated with short survival. The 5-year BCSS and OS rates were significantly lower in patients with breast cancer as the second primary cancer than in those with breast cancer as the prior cancer in both the standard and PSM analyses, these results are AGING Patients who received underwent chemotherapy for prior cancer may not respond well to systemic treatment for their second primary cancer due to decreased efficacy and tolerability after prior systemic treatment [33,34]. Interestingly, Fine and Gray's regression analysis showed that breast cancer treatment was associated with a decreased risk of BCSM.…”
Section: Discussionmentioning
confidence: 83%
“…In Our results showed that breast cancer as the second primary cancer was associated with short survival. The 5-year BCSS and OS rates were significantly lower in patients with breast cancer as the second primary cancer than in those with breast cancer as the prior cancer in both the standard and PSM analyses, these results are AGING Patients who received underwent chemotherapy for prior cancer may not respond well to systemic treatment for their second primary cancer due to decreased efficacy and tolerability after prior systemic treatment [33,34]. Interestingly, Fine and Gray's regression analysis showed that breast cancer treatment was associated with a decreased risk of BCSM.…”
Section: Discussionmentioning
confidence: 83%
“…Nevertheless, breast-conserving surgery (BCS) has some limitations in clinical practice, and the need for radiotherapy after surgery causes many patients to lose their motivation for BCS [8,9]. On the other hand, traditional modified radical mastectomy (MRM) significantly increases the occurrence of complications such as upper limb edema and paraesthesia, and the surgical scar from on the chest and the axilla will affect the esthetics and limit the movement of the shoulder joint to some extent [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a greater risk of MPC among patients with an initial diagnosis of breast cancer at the age of < 50 years and in Black women with an ER-/PR-status than in Other patients [10] . A clinical study reported that the use of systemic therapy did not increase the risk of MPC [11] , while a nested case-control study using the SEER database suggested that radiotherapy (HR = 1.33) was related to the risk of second primary malignancy after BC [12] .…”
Section: Introductionmentioning
confidence: 99%